Gender Roles, Implications for Water, Land, and Food Security in a Changing Climate: A Systematic Review - Tantoh, Henry Bikwibili; McKay, Tracey T. J. M.; Donkor, Felix Ekwabena; Simatele, Mulala Danny (Frontiers in Sustainable Food Systems, 2021)
Water and land are vital resources essential to ensuring sustainable and productive rural economies. They are also essential for safeguarding food security and socio-economic development. In spite of this, the concept of water-land-food security nexus has generally been examined from a top-down manner with women mostly disenfranchised in the access and management of water and land in particular. Concurrently, risks linked with climate crisis aggravate gender inequalities. The limited access to resources, restricted formal rights through top-down management exacerbates the vulnerability of poor rural women. Furthermore, policy development procedures follow a sectoral approach with no account of interrelationship and interdependence between the sectors. This, directly and indirectly, limits the stewardship of natural resources and mitigation of the effects of climate change. This study, therefore, examines gender roles and their implications for water, land and food security in a changing climate through an integrative systematic review of literature in Sub-Saharan Africa. It further explains the importance to consider the nexus in adaptation. Food security and sustainable livelihoods could be ensured if women can freely and adequately access land and participate in decision-making processes.